Has punishment played a role in the evolution of cooperation? A critical review - Baumard, N (Springer, 2010)
In the past decade, experiments on altruistic punishment have played a central role in the study of the evolution of cooperation. By showing that people are ready to incur a cost to punish cheaters and that punishment help to stabilise cooperation, these experiments have greatly contributed to the rise of group selection theory. However, despite its experimental robustness, it is not clear whether altruistic punishment really exists. Here, I review the anthropological literature and show that hunter-gatherers rarely punish cheaters. Instead, they avoid dealing with them and switch to other partners. I suggest that these data are better explained by individual selection and in particular by partner choice models, in which individuals are in competition to be recruited by cooperative partners. I discuss two apparent problems for partner choice theories: large-scale cooperation and punishments in economic games. I suggest that rather than favouring group selection theory, these two phenomena provide evidence in favour of individual selection: (1) people produce large-scale cooperation through institutions in which punishment is not altruistic but rewarded on an individual basis; (2) punishment in experimental games can be explained without altruism and is indeed often better explained by individual interests.